Photosynthesis-based biosensors for environmental analysis of herbicides - Amina Antonacci (Elsevier, 2021)
It is generally agreed that photosynthetic organisms demonstrated their potential for the development of highly sensitive, sustainable, and affordable biosensors to detect toxic chemicals in aquatic ecosystems, being a primary target for most toxic pollutants. Based on this principle, the application of photosynthetic material as a biological receptor in biosensing provides an excellent tool for a cheap and effective detection of a wide range of life-threatening pollutants. This review will provide a comprehensive overview of photosynthesis-based biosensors, shading light on the diverse types of photosynthetic materials to be exploited, the different supports on which such material can be immobilized, and the dual opto-electrochemical transduction in which it can be integrated for the environmental monitoring of photosynthetic herbicides.